Strategies Implemented by Bawaslu Mataram City to Prevent Money Politics in the 2024 General Election - Rohani, Wanda Dwi; Sumardi, Lalu; Kurniawansyah, Edy (Jurnal Penelitian Medan Agama, 2025)
This study aims to analyze the strategies implemented by the Elections Supervisory Agency (Bawaslu) to suppress vote buying practices. This research employed qualitative methods with a descriptive-analytical approach, incorporating interviews and documentation. The results indicate that Bawaslu has adopted several core strategies, including strengthening participatory oversight, providing political education to the public, enhancing the capacity of election supervisors, and collaborating with law enforcement agencies. However, implementation faces significant challenges, such as limited human resources, low political awareness among the public, and difficulties in proving vote buying cases.